Central Asia: The Vanguard in Jointly Building the «Belt & Road» Community of Shared Future for Mankind - Tongqian Zou; Xiaorong Hu; Mengya Zhang (Ukrainian Policymaker, 2023)
The Silk Road originated in China, while Central Asia served as the crossroads of the Eurasian region. In 140 BC, during the Han Dynasty, Zhang Qian embarked on a mission to the Western Regions, present-day Central Asia. He paved the way from the East to the West, completing a challenging journey. President Xi proposed constructing the Silk Road Economic Belt (SREB) in Kazakhstan, making Central Asia the starting point and the first western station of the Belt and Road Initiative (BRI). Central Asia has always been at the forefront of building the BRI, setting an example for constructing a community with a shared future for humanity.